Pandangan tentang Kreativitas Guru Pembelajar Sebuah Upaya Motivasi Belajar Siswa - Ahmad Syafi'i (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Teacher's creativity is the ability to create something new, unique, true, useful and valuable in learning possessed by an educator (teacher) for educational purposes, with the creativity that is owned by a teacher will be able to foster students' motivation. Student motivation can grow due to a creative learning environment and fun. Factors that make a creative and enjoyable learning is the learning objectives are appropriate, meaningful subject matter, teaching methods varied, diverse teaching media and proper evaluation. whereas these factors can only be found in the figure of a creative teacher. Teachers in schools should be able to apply some of the forms and methods mentioned above in order to increase the motivation of learners to study the subject matter.Keywords: The creativity of teachers, students' motivation